Testing Pneumonia Vaccines in the Elderly: Determining a Case Definition for Pneumococcal Pneumonia in the Absence of a Gold Standard. Issue 6 (3rd January 2018) - Jokinen, Jukka; Snellman, Marja; Palmu, Arto A; Saukkoriipi, Annika; Verlant, Vincent; Pascal, Thierry; Devaster, Jeanne-Marie; Hausdorff, William P; Kilpi, Terhi M
Abstract: Clinical assessments of vaccines to prevent pneumococcal community-acquired pneumonia (CAP) require sensitive and specific case definitions, but there is no gold standard diagnostic test. To develop a new case definition suitable for vaccine efficacy studies, we applied latent class analysis (LCA) to the results from 7 diagnostic tests for pneumococcal etiology on clinical specimens from 323 elderly persons with radiologically confirmed pneumonia enrolled in the Finnish Community-Acquired Pneumonia Epidemiology study during 2005–2007. Compared with the conventional use of LCA, which is mainly to determine sensitivities and specificities of different tests, we instead used LCA as an appropriate instrument to predict the probability of pneumococcal etiology for each CAP case based on individual test profiles, and we used the predictions to minimize the sample size that would be needed for a vaccine efficacy trial. When compared with the conventional laboratory criteria of encapsulated pneumococci in culture, in blood culture or high-quality sputum culture, or urine antigen positivity, our optimized case definition for pneumococcal CAP resulted in a trial sample size that was almost 20, 000 subjects smaller. We believe that the novel application of LCA detailed here to determine a case definition for pneumococcal CAP could also be similarly applied to other diseases without a gold standard.